2005
DOI: 10.1172/jci200521948
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of α-defensin-1 in anti–HIV-1 innate immunity

Abstract: α-Defensins are abundant antimicrobial peptides in polymorphonuclear leukocytes and play an important role in innate immunity. We have previously shown that α-defensin-1 can inhibit HIV-1 replication following viral entry. Here we examined the molecular mechanism(s) of α-defensin-1-mediated HIV-1 inhibition. α-Defensin-1 had a direct effect on HIV-1 virions at a low MOI in the absence of serum. The direct effect on HIV-1 virions was abolished by the presence of serum or an increase in virus particles. Studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Similar ability to reduce cell-to-cell spread has been reported for a-helical interferon [184]. Although still controversial, it has been suggested that a-defensin-1 is the soluble CD8 + T-cell antiviral factor with potent activity against HIV [185]. Similar immune activating properties are also hypothesized for Lfcin and other cationic peptides.…”
Section: The Cellular Target and Antiviral Mode Of Action Of Lfcinsupporting
confidence: 57%
“…Similar ability to reduce cell-to-cell spread has been reported for a-helical interferon [184]. Although still controversial, it has been suggested that a-defensin-1 is the soluble CD8 + T-cell antiviral factor with potent activity against HIV [185]. Similar immune activating properties are also hypothesized for Lfcin and other cationic peptides.…”
Section: The Cellular Target and Antiviral Mode Of Action Of Lfcinsupporting
confidence: 57%
“…Whereas the former report indicated that hBD-2 and hBD-3 downregulate the HIV-1 coreceptor CXCR4 in PBMC and T lymphocytes, suggesting inhibition of the X4 virus by β-defensins at the viral entry step [139], authors of the latter did not observe receptor down-regulation by hBD-2, and suggested instead that a post-entry, intracellular signaling event is responsible for the inhibition of HIV-1 replication [138]. The idea of intracellular signaling involvement is reminiscent of studies on inhibition of HIV replication by related human neutrophil α-defensins [141,142]. Despite the differences in the interpretation of inhibition at the cellular level, β-defensins can directly inactivate HIV-1 virions [138,139].…”
Section: Anti-hiv Effectmentioning
confidence: 99%
“…Due to their lectin-like properties, HNP1-3 can bind with relatively high affinity to HIV viral gp120 and CD4 receptors . Meanwhile, as a non-competitive inhibitor of protein kinase C (PKC), HNP1 may have a potential role against HIV-1 via interfering with PKC signaling pathways and blocking nuclear import and transcription of the HIV-1 genome (Chang et al 2005). The anti-HIV activities of HBDs remain unclear; however, studies have demonstrated that that HBD2 and HBD3 expression was significantly upregulated in both HIV-positive and HIV-negative men who have sex with men (Kreuter et al 2009).…”
Section: Antimicrobial Activities Of Defensinsmentioning
confidence: 99%